AB1334-HPR BARRIERS AND FACILITATORS TO PHYSICAL ACTIVITY IN JUVENILE IDIOPATHIC ARTHRITIS (JIA): A SCOPING REVIEW. (2nd June 2020) - O Donoghue, K.; Larkin, L.
Abstract : Background: Physical activity is an important aspect in the management of JIA (1). However physical activity levels are low in this population (2). Limited research has been conducted to identify definitive barriers and facilitators to physical activity in children and adolescents who have JIA. Objectives: The objective of this scoping review was to identify the common barriers and facilitators to physical activity in JIA. Methods: Original studies, either quantitative or qualitative, including participants with a diagnosis of JIA, who were under 18 years of age were included. Two independent reviewers carried out a search of the literature and full text reviews of papers to determine eligibility for inclusion. The Critical Skills Appraisal Programme (CASP), Appraisal tool for Cross-Sectional Studies (AXIS) and Downs and Black critical appraisal tools were used to assess the quality of the included research articles. Results: Eighteen studies were included in the review. The included studies were of a variety of low, moderate and high quality. The synthesis of the data identified pain to be the most common barrier and the modification of physical activities to the need of the individual to be the most common facilitator to physical activity in JIA. Conclusion: Identifying the most common barriers and facilitators to physical activity allows clinicians to apply better management strategies when treating an individual with JIA. Our findings demonstrate the need for further research in this area to assist increasing physical activity participation for children and adolescents who have JIA. References: [1]Kuntze, G., Nesbitt, C., Whittaker, J.L., Nettel-Aguirre, A., Toomey, C., Esau, S., Doyle-Baker, P.K., Shank, J., Brooks, J., Benseler, S., Emery, C.A. (2018) 'Exercise Therapy in Juvenile Idiopathic Arthritis: A Systematic Review and Meta-Analysis', Archives of Physical Medicine and Rehabilitation, 99(1), 178-193 [2]Bos, G.J.F.J., Lelieveld, O.T.H.M., Armbrust, W., Sauer, P.J.J., Geertzen, J.H.B., Dijkstra, P.U. (2016) 'Physical activity in children with Juvenile Idiopathic Arthritis compared to controls', Pediatric Rheumatology, 14(1), 42. Disclosure of Interests: None declared